Context and contact: a comparison of patient and family engagement with early intervention services for psychosis in India and Canada. Issue 8 (28th June 2022) - Iyer, Srividya N.; Malla, Ashok; Taksal, Aarati; Maraj, Anika; Mohan, Greeshma; Ramachandran, Padmavati; Margolese, Howard C.; Schmitz, Norbert; Joober, Ridha; Rangaswamy, Thara
Abstract: Background: It is unknown whether patient disengagement from early intervention services for psychosis is as prevalent in low- and middle-income countries (LMICs) like India, as it is in high-income countries (HICs). Addressing this gap, we studied two first-episode psychosis programs in Montreal, Canada and Chennai, India. We hypothesized lower service disengagement among patients and higher engagement among families in Chennai, and that family engagement would mediate cross-site differences in patient disengagement. Methods: Sites were compared on their 2-year patient disengagement and family engagement rates conducting time-to-event analyses and independent samples t tests on monthly contact data. Along with site and family involvement, Cox proportional hazards regression included known predictors of patient disengagement (e.g. gender). Results: The study included data about 333 patients (165 in Montreal, 168 in Chennai) and their family members (156 in Montreal, 168 in Chennai). More Montreal patients (19%) disengaged before 24 months than Chennai patients (1%), χ 2 (1, N = 333) = 28.87, p < 0.001. Chennai families had more contact with clinicians throughout treatment (Cohen's d = −1.28). Family contact significantly predicted patient disengagement in Montreal (HR = 0.87, 95% CI 0.81–0.93). Unlike in Chennai, family contact declined over time in Montreal, with clinicians perceiving such contact as not necessary (Cohen's d = 1.73). Conclusions: This is the first investigation of early psychosis service engagement across a HIC and an LMIC. Patient and family engagement was strikingly higher in Chennai. Maintaining family contact may benefit patient engagement, irrespective of context. Findings also suggest that differential service utilization may underpin cross-cultural variations in psychosis outcomes.